Face of Christ - Claude Mellan (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Face of Christ. Engraving created from a single spiralling line that starts at the tip of Jesus's nose. Also known as Veil of Veronica .
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons